2019
DOI: 10.1001/jamasurg.2018.4334
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Patterns, and Outcomes of Late Recurrence After Liver Resection for Hepatocellular Carcinoma

Abstract: IMPORTANCE Late recurrence (more than 2 years) after liver resection for hepatocellular carcinoma (HCC) is generally considered as a multicentric tumor or a de novo cancer. OBJECTIVE To investigate the risk factors, patterns, and outcomes of late recurrence after curative liver resection for HCC. DESIGN, SETTING, AND PARTICIPANTS This study was a multicenter retrospective analysis of patients who underwent curative liver resection for HCC at 6 hospitals in China from January 2001 to December 2015. Among 734 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
296
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(317 citation statements)
references
References 41 publications
16
296
5
Order By: Relevance
“…In the multivariate analysis, maximal tumor diameter (diameter > 5 cm), tumor number (n > 1), and without preoperative TACE predicated poor OS for HCC. The results were in accordance with the previous report [28,29]. For LTP, the multivariate analysis showed that more sessions, lower αfetoprotein level and 3D planning were associated with better LTP controlling, which indicated that precision of treatment was vital in HCC.…”
Section: Discussionsupporting
confidence: 91%
“…In the multivariate analysis, maximal tumor diameter (diameter > 5 cm), tumor number (n > 1), and without preoperative TACE predicated poor OS for HCC. The results were in accordance with the previous report [28,29]. For LTP, the multivariate analysis showed that more sessions, lower αfetoprotein level and 3D planning were associated with better LTP controlling, which indicated that precision of treatment was vital in HCC.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, sex represented a large weighting in the nomogram for RFS and was significantly associated with HCC recurrence. Previous studies have found that men were more likely to develop HCC than women, and male patients were more prone to relapse than female patients in 2 years after hepatectomy . This sex difference may be related to sex hormones and requires additional study.…”
Section: Discussionmentioning
confidence: 92%
“…Tumor size was positively correlated with the tumor recurrence, especially for those with a diameter greater than 5 cm . This effect may be related to the fact that larger tumors more likely to result in intrahepatic metastasis and vascular invasion .…”
Section: Discussionmentioning
confidence: 93%
“…The median survival time of patients after recurrence was only 8 months. The primary goal of postoperative follow ups was to improve survival by promoting early detection of recurrence in asymptomatic stages . This reflects the need for regular follow ups and early diagnosis of recurrence for more targeted treatment.…”
Section: Discussionmentioning
confidence: 99%